Reduction of scrap percentage of cast parts by optimizing the process parameters - Chandrasekaran, Rakesh (2019)
Casting is a widely used manufacturing process in the automotive industry. Die casting is the most popular type of casting processes. But the fact observed in many industries is the scraps or wastages occurring after the process. Thus, this thesis is primarily based on understanding the die-casting process and the factors governing them. In this study, the part to be studied is a throttle body. The raw material used for the production is AlSi9Cu3. The main concern in this part is the occurrence of defects such as bad filling, heat bubbles, and porosity. Thus, it is important to perform process optimization. Techniques or methods such as Design of Experiments, ANOVA analysis, and numerical simulations are used. This thesis also focuses on the use of brainstorming as an industrial discussion tool and the use of quality tools for process optimization. Thus, these techniques are utilized in order to eliminate the defects. The scrap after using these techniques and methods is reduced to 9% from 14% initially found. This investigation has been performed as a continuous improvement project in Sonafi and as a master thesis for “Instituto Superior de Engenharia do Porto”.